KYAI AS A PSYCHOLOGIST OF ISLAMIC BOARDING SCHOOLS: AN EXPLORATION OF THE ROLE OF LEADERSHIP IN STUDENT COUNSELING - Musslifah, Anniez Rachmawati; Putri, Dhian Riskiana; Puspita, Aghi Viona Semas (Counsenesia Indonesian Journal Of Guidance and Counseling, 2025)
Kyai has a very dominant role in guiding and fostering students and the surrounding community. In Islamic counseling practice, Kyai generally applies the method of dhikr and ibrah as a means to help counselors overcome their problems. In fact, almost every problem faced by counseling is directed to do more dhikr and remember Allah as a form of spiritual solution. This research aims to explore the direct experience of the Kyai in dealing with students who experience various problems. This is useful in raising a new dimension in the study of Kyai's leadership, namely as a figure who plays a role in guiding and directing students through a counseling approach. With in-depth interview techniques and participatory observation, this study will present a real picture of counseling practices in Islamic boarding schools and the various challenges faced by Kyai in carrying out this role. The results of the study show that the counseling approach carried out by Kyai in Islamic boarding schools has its own characteristics that distinguish it from modern counseling approaches. By referring to Islamic books, Kyai instills spiritual values in every guidance given, so that students not only get solutions to their problems, but also gain a deeper understanding of the meaning of life.